THEATER AND MUSIC CULTURE IN THE KHRUSHCHEV THAW IN KUBAN AND STAVROPOL TERRITORIES - N. Romanova (Гуманитарные и юридические исследования)
The author examines the process of the impact of a new political course of the Khrushchev Thaw era on the state of Soviet culture and the specifics of the cultural policy of the party and state leadership in the context of its implementation on the ground using the example of the activities of professional theater and entertainment associations Krasnodar and Stavropol Territories. The work analyzes the process of formation of new directions in music repertoire, theatrical performances and pop repertoire in the context of regional themes. The problem of attracting local authors was the main because party instruction. It required that pop programs and theatrical performances based on local material were supposed not only to "bring a positive character onto the stage" as an example for the workers, but this character should be understandable and close to local residents. In the spirit of the unity of theory and practice, proclaimed by the new party leaders, the use of images of positive characters from the locals will lead to an increase in the enthusiasm of workers, and, therefore, to the rise of regional economy. The author paid attention to the revitalization of activity in the late 1950s - early 19600s of musical and theatrical public organizations of the Southern province by the example of local branches of the All-Russian Choral and All-Union Theater Societies. Based on the analysis of sources, the multifaceted work of professional theatrical and entertainment associations of the Kuban and Stavropol regions on the artistic education of young spectators is shown; new forms of this work are highlighted. The author paid special attention to the expansion of this activity in the villages of the Kuban and Stavropol regions. The article traces the previously unprecedented process of the development of amateur art and, on its basis, the identification of folk talents. Together with the patronage of professional actors, musicians, directors, this led to the emergence in the regions of high-quality musical and theatrical training from among local residents and the creation of powerful creative teams that could compete with professionals. The consequence of this was the assignment of the status of professional and even academic ensembles and theaters to the best amateur ensembles. Within the framework of this article, the question is raised about such a new phenomenon in the artistic life of the southern province of the the Khrushchev Thaw epoch, as the organization of tours of foreign artists in the cities of Stavropol and Kuban.